EFFECTS OF RECOGNITION AND REWARD ON EMPLOYEE LOYALTY - Dr. K C Prashanth,; Dr. Veena M, (EPRA International Journal of Research and Development (IJRD), 2022)
As opined, loyalty of employee is directly proportional to royalty of an organization. Positive stimulus has a profoundable impact on the individuals and in turn on their output. Positive environment has positive effect on employees, positive employees have impact on their work, and positive work has impact on the customer and consumers. Positive stimulus may be in terms of promotion, bonus, financial and non financial rewards and all in all recognition and rewarding mechanism. Employees should be recognised and rewarded by their contributions to the organisation, their skills and experience, irrespective of age, gender or any other traits which unrelated to the function they perform. Many managers favour recognition such as letters of recommendation, tokens of appreciation, flowers and mention in companies’ news letters or paying for employee’s participation. It is believed that monetary incentives can easily detract workers from the proper meaning of the employees suggestion scheme. One of the crucial determent in successful implementation of TQM is recognition and reward. MSMEs play critical role in the economic development of a country. Quality management of these MSMEs is would be critical for their stability. The aim of the paper is to examine the level of Recognition and reward on Employee loyalty at MSMEs in Ballari, Karnataka. The universe comprised executive and non executive workforce of the firm. Sampling was carried out using convenient sampling technique with sample size of 50 in line with the Cochran formula. Data was collected using observation and informal interview methods. Descriptive statistics and Chi-square test was used to analyse the data. The research envisaged that all the factors of Recognition and reward are associated with Employee loyalty at the MSMEs. The study revealed that, Moral awards and performance linkage to benefits at the MSMEs has significant influence on Employee loyalty.